Limits to growth: human economy and planetary boundaries - Kerryn Higgs (The Journal of Population and Sustainability, 2017)
The idea of physical limits to human economic systems is advanced by physical scientists and ecological economists, as well as appealing to the common sense proposition that unending growth in physical processes such as material extraction and waste disposal will ultimately be inconsistent with any finite entity, even one as large as the Earth. Yet growth remains the central aim of business and government almost everywhere. This paper examines the history of the idea of economic growth and the many influences and interests that supported – and still support – its enshrinement as the principal aim of human societies. These include the apparatus of propaganda in favour of corporate interests; the emphasis on international trade; the funding of environmental denial; and, underlying all these, the corporate requirement for profit to continue to increase. The dominance of these influences has serious consequences for the natural world while growth has failed to solve the problems of poverty.